A study on the pattern of maxillofacial injury in patients reporting to a tertiary care hospital in eastern Nepal. Issue 5 (September 2015) - Pradhan, Leeza; Jaisani, Mehul R.; Dulal, Sanad; Dongol, Ashok; Sagtani, Alok
Abstract: Maxillofacial injuries occur in a significant number of trauma patients. They occur as isolated injuries or as a part of multiple injuries to other parts of the body as well. The cause of injury may vary from road traffic accidents, physical assault, sports injury to domestic/industrial accidents and blast injuries. The aim of this study was to identify the epidemiological profile, causes and pattern of maxillofacial injuries. Data from all the patients visiting the Emergency department, BPKIHS, with maxillofacial injuries were analyzed. The variables like age, gender, cause of injury, nature of injuries, and associated injury if any were recorded. The highest incidence of maxillofacial injuries was observed in the age group of 21–30 years, with males outnumbering females in all age groups. Road traffic accident was the most common cause of maxillofacial injury. 10% of the injuries occurred under alcoholic influence. Soft tissue injuries were the most common pattern of injuries. Among bony fractures, the mandible was the most frequently fractured bone. The findings of this study indicate the need for strict implementation of traffic rules, improvement of road conditions and education regarding alcohol abuse for minimizing the risk of maxillofacial injuries.